The 45th anniversary of Cancer Research Institute, Tomsk National Research Medical Center of the Russian Academy of Sciences - E. L. Choinzonov; S. A. Nekrylov; N. V. Cherdyntseva; V. I. Chernov; V. E. Goldberg (Сибирский онкологический журнал, 2024)
.